Time Dependent Production of Cytokines and Eicosanoids by Human Monocytic Leukaemia U937 Cells; Effects of Glucocorticosteroids - Ingrid M. Garrelds; Peter Th. W. Van Hal; Raquel C. Haakmat; Henk C. Hoogsteden; Pramod R. Saxena; Frederik J. Zijlstra (Mediators of Inflammation)
In the present study the human monoblast cell line U937 has been used as a model to study the function of human mononuclear phagocytes in asthma. The kinetics of the production of eicosanoids and cytokines, which are thought to play a role in the pathogenesis of asthma, were studied. In addition, the effects of glucocorticosteroids were investigated, as these drugs are of great importance for the treatment of asthmatic patients. After stimulation with phorbol-12 myristate acetate (PMA) for 24h, U937 cells were cultured in the absence or presence of lipopolysaccharide (LPS: 1 and 5 μg ml-1) and glucocorticosteroids (budesonide, fluticasone propionate and prednisolone: 10-11, 10-9 and 10-7 M) for 96h. The production of interleukin- 1β (IL-1β), interleukin-6 (IL-6), prostaglandin E2 (PGE2) and thromboxane B2 (TxB2) gradually increased in time after stimulation with LPS, whereas the transient production of tumor necrosis factor alpha (TNF-α) reached its maximum between 6 and 12 h. Interferon-gamma (IFN-γ), interleukin-10 (IL-10) and leukotriene B4 (LTB4) were not detectable. All three glucocorticosteroids (budesonide, fluticasone propionate and prednisolone) completely inhibited the production of both eicosanoids and cytokines. The production of eicosanoids was more sensitive to these glucocorticoids than the production of cytokines. The observed differences in the kinetics of the production of eicosanoids and cytokines stress the importance of time course experiments in studies on the effect of drugs on mononuclear cells.